Using the NICE Framework as a Metric to Analyze Student Competencies (Journal of The Colloquium for Information Systems Security Education, 2020)
This paper describes how the Department of Energy’s CyberForce Competition™ uses anomalies to map collegiate teams’ comprehension of different topics in cybersecurity. The competition is currently in its fourth iteration with a fifth planned in November 2019. Anomalies are challenges that collegiate teams must solve in order to receive points and vary in nature, timing, and skillset. All successful teams are able to manage the scale and prioritize which anomalies to complete. This paper identifies which NICE pillars students scored in the upper percentile, and which topics students averaged a lower score. These results may help educators in creating training programs, classes and curriculum to help close these knowledge gaps.
Keywords: NICE Framework; CyberForce; anomalies; competencies; competition